A significant vascular variant in oncologic pancreaticoduodenectomy: the arc of Buhler - L. Schumacher; H. C. Albrecht; S. Gretschel (Surgical Case Reports, 2022)
Abstract Background The arc of Buhler (AOB), a rare anastomosis connecting the superior mesenteric artery (SMA) to the celiac trunk (CA), was found in a patient suffering from an adenocarcinoma of the pancreatic head. Case presentation Oncologic pancreaticoduodenectomy required resection of the AOB to achieve complete tumor removal. After an uneventful clinical course in the first days, the patient suffered a severe complication. Due to ischemia of the stomach and spleen, complete resection of the stomach, spleen, and remaining pancreas had to be performed. Conclusions The hemodynamic impact of this arterial variant has been discussed mainly for liver perfusion, which remained intact at all times in our case. Because of the serious obstacles mentioned above, we strongly recommend that the presence of AOB be considered in preoperative diagnosis and preservation when possible. If the AOB is likely to be ligated, stenosis of the SMA or CA should be excluded and resolved before surgery.